Challenges in Agro-Climate and Ecosystem - Saifullah, Muhammad; Tardio, Guillermo; Mickovski, Slobodan B. (IntechOpen, 2022)
Due to an increasing population and rapid urbanization, crop production demand is high, and global food security is at risk. Challenges such as rising temperatures and environmental degradation need to be addressed quickly and effectively. This book discusses agriculture, climate change, and the ecosystem in the context of the United Nations Sustainable Development Goals. Chapters examine the various types of environmental stressors that negatively impact crop yield (drought, salinity, high temperatures) and how to mitigate them. They also present case studies from different parts of the world.